2013
DOI: 10.1111/iej.12136
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between oral infections and blood glucose concentrations or HbA1c levels in normal and diabetic rats

Abstract: Oral infections affect glycaemic conditions in diabetic rats and increase HbA1c levels in normoglycaemic or diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 45 publications
8
70
0
2
Order By: Relevance
“…These findings are in accordance with those of Cintra et al (14), who reported no difference in serum glucose concentration between rats with periapical inflammation and control rats. However, our results do not corroborate the findings of Bain et al (16), who affirmed that blood glucose and insulin concentrations were significantly higher in pregnant rats with induced chronic pulpal abscesses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in accordance with those of Cintra et al (14), who reported no difference in serum glucose concentration between rats with periapical inflammation and control rats. However, our results do not corroborate the findings of Bain et al (16), who affirmed that blood glucose and insulin concentrations were significantly higher in pregnant rats with induced chronic pulpal abscesses.…”
Section: Discussionsupporting
confidence: 93%
“…Periapical lesions (PLs) induce oral inflammation and immune responses against microorganisms that invade and destroy the dental pulp (14). TNF-a expression at inflammation sites increases after pulp exposure (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data in Figure 3 demonstrated that the level of HbA1c% was elevated in STZdiabetic rats, compared to the corresponding normal rats. Our result was in agreement with the previously reported which stated that plasma HbA1c levels were higher in diabetic rats than in normal groups [46]. The observed increase in the levels of HbA1c% in diabetic control group rats is due to the presence of excessive amounts of blood glucose.…”
Section: Discussionsupporting
confidence: 94%
“…However, the relationship between these infections and systemic diseases has not been completely understood, and systemic alterations arising due to correlation between endodontic diseases and diabetes mellitus are being investigated (Kodama et al 2011, Cintra et al 2014, Segura-Egea et al 2015. It has been reported that increases in blood glucose concentrations (hyperglycaemic state) are directly associated with the reduction in metabolic control in diabetes which may accelerate the development and progression of apical periodontitis and periodontal disease (Kodama et al 2011, Cintra et al 2014, Segura-Egea et al 2015. Furthermore, Cintra et al (2014) reported that after 30 and 60 days of oral infection, there was an increase in blood glucose concentrations in diabetic animals.…”
Section: Introductionmentioning
confidence: 99%